2016
DOI: 10.1519/jsc.0000000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Interset Rest Intervals on Performance of Single and Multijoint Exercises With Near-Maximal Loads

Abstract: The aim of this study was to investigate the acute effects of different interset rest intervals on performance of single- and multijoint exercises with near-maximal loads. Fifteen trained men (26.40 ± 4.94 years, 79.00 ± 7.10 kg, 176.6 ± 6.06 cm, 11.80 ± 2.47% body fat, and bench press relative strength: 1.26 ± 0.19 kg·kg of body mass) performed eight sessions (2 exercises × 4 interset rest intervals); each consisting of 5 sets with a 3RM load. The exercises tested were the machine chest fly (MCF) for the sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 9 publications
2
29
0
4
Order By: Relevance
“…The one maximum repetition test (1-RM) was used as a measure of Pre-, Mid-and Post-training upper-body strength on two non-consecutive days (each day for each exercise) using the bench press (BP) and triceps pull-down (TP; 2 sessions for 1-RM tests). Following the test, if individuals exceeded or did not completed one repetition with the stipulated intensity, adjustments in load were made for each subject, and a new attempt was performed with a rest period no shorter than 5-minutes (Scudese et al, 2015;Senna et al, 2016). The resistance was progressively increased (2 kg) after each successful attempt until failure.…”
Section: Strength Testmentioning
confidence: 99%
“…The one maximum repetition test (1-RM) was used as a measure of Pre-, Mid-and Post-training upper-body strength on two non-consecutive days (each day for each exercise) using the bench press (BP) and triceps pull-down (TP; 2 sessions for 1-RM tests). Following the test, if individuals exceeded or did not completed one repetition with the stipulated intensity, adjustments in load were made for each subject, and a new attempt was performed with a rest period no shorter than 5-minutes (Scudese et al, 2015;Senna et al, 2016). The resistance was progressively increased (2 kg) after each successful attempt until failure.…”
Section: Strength Testmentioning
confidence: 99%
“…The rest period between sets has become nowadays an important resistance training variable to be considered within programs ( de Salles et al, 2009 ; Paoli and Bianco, 2015 ; Pescatello, 2014 ; Villanueva et al, 2015 ). It has been demonstrated that its manipulation could trigger distinct neuromuscular ( Senna et al, 2011 , 2012 , 2016 ), endocrine ( Gonzalez et al, 2015 ; Rahimi et al, 2010 ), cardiorespiratory ( Ratamess et al, 2007 ) and inflammatory responses ( Rodrigues et al, 2010 ; Zajac et al, 2015 ). A number of studies have been carried out in order to refine the time-efficiency of a given workout while maintaining a high level of performance ( de Salles et al, 2010 ; Senna et al, 2016 ; Willardson and Burkett, 2005 , 2006b , 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with 10-RM intensities 14,19,27,29 demonstrated increases in RPE during consecutive sets, and these increases were more evident at shorter intervals (1 minute) when compared to longer intervals long (3 and 5 minutes). More recently, it was observed significant increases in RPE at 1-minute intervals from the third set of single and multi-joint exercises with a 3-RM intensity 21 . These results suggest a better perception of fatigue in shorter when compared with larger rest periods, independently of the exercise modality (single or multi-joint).…”
Section: Discussionmentioning
confidence: 94%
“…Posteriorly, all subjects completed five sets of a pre-established upper limb exercise session (BP, MCF, and TP) with loads of 15-RM with 1 minute of rest interval between sets. Warm-up before the resistance exercise session consisted of two sets of 12 repetitions with a 40% load of 15-RM for the BP exercise 21 . It was respected two-minute of rest between warmup and the intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation